Risk factors for jockey falls in Japanese thoroughbred jump racing - Mizobe, F.; Takahashi, Y.; Kusano, K. (Journal of Equine Veterinary Science, 2022)
Jockey safety is an important subject from a welfare perspective and public perception. This is the first retrospective case-control study that aims to identify risk factors associated with jockey falls (JF) in Thoroughbred jump races held by the Japan Racing Association (JRA). JF in 17,459 maiden-class race starts at eight racecourses from 2003 to 2017 were retrospectively reviewed. Data were extracted from a database and official accident reports maintained by the JRA. Thirteen possible risk factors were evaluated using multivariable logistic regression to identify those that were significantly associated with JF. A total of 724 JF were recorded, with an incidence rate of 41.5 falls per 1,000 starts (95% CI: 38.6-44.5). Final model included stable, horse age, year, season, course, horse sex, horse experience, and jockey experience. No two-way interactions were observed. Six risk factors were significantly associated with JF: Year (2003-2007 or 2008-2012 > 2013-2017; P = .0011), season (spring, autumn, or winter > summer; P = .0006), course type (dual direction > single direction; P < .0001), horse sex (female > male or gelding; P = .0003), horse experience (inexperienced horse > experienced horse; P < .0001) and jockey experience (apprentice jockey > experienced jockey; P = .0332) significantly affected the odds of JF. In agreement with overseas reports, our results suggest that the occurrence of JF is multifactorial and associated with jockey- and horse-related factors as well as environmental factors. To safeguard the welfare of jockeys, implementation of measures according to identified risk factors is recommended.